Upaya Sekuritisasi Pemerintah Bangladesh Terhadap Keberadaan Pengungsi Rohingya - Pertiwi, Yuliana Indra (Nation State: Journal of International Studies, 2021)
The prolong existence of Rohingya Refugees in Bangladesh had caused several problems and threatened its national security and people of Bangladesh. Bangladesh Government as securitizing actor take securitization act to protect its national security and people of Bangladesh based on policies made. This research use securitization theory or Copenhagen School to enlightened Bangladesh Government actions to securitize its national security and people of Bangladesh upon the problem caused by the existence of Rohingya refugees in Bangladesh. This research uses qualitative methods with books and journal articles related as data sources. The result of this research shows Bangladesh government actions to securitize its national security and people of Bangladesh based on its policies is the best way for both parties to repress the broadening of existing problem.